A Correlational Study on Representational Abilities and Mathematical Connections in Junior High School - Fredi Ganda Putra; Sunyono Sunyono; Een Yayah Haenilah; Hasan Hariri; Dewi Lengkana; Nurhanurawati Nurhanurawati (STAI Hubbulwathan Duri, 2023)
Mathematical representation and connection ability are part of the student's ability. Because of their low ability, educators will find it difficult to determine learning tools in the classroom. Therefore, finding a link between the two abilities is necessary to make it easier for teachers to prepare lessons. This study aims to determine the relationship between representational abilities and students' mathematical connections. The population in this study were all grade eight students at a state junior high school in Merbau Mataram, with a total sample of 34 selected using a class random sampling technique. The research instrument was a mathematical representation test and a connection ability test with a total of six questions. Data analysis used the correlation coefficient test of the Pearson/Product Moment formula. The results showed a significant relationship between students' mathematical representation ability and the overall connection. This means that the ability of mathematical representation is directly proportional to the ability of mathematical connections. The higher the student's mathematical representation ability, the higher the student's connection ability, and vice versa. Teachers can focus on preparing learning tools for one of these two abilities.